2013
DOI: 10.1038/cdd.2013.128
|View full text |Cite
|
Sign up to set email alerts
|

A feed-forward loop involving Trib3, Akt and FoxO mediates death of NGF-deprived neurons

Abstract: The mechanisms governing neuron death following NGF deprivation are incompletely understood. Here, we show that Trib3, a protein induced by NGF withdrawal, has a key role in such death via a loop involving the survival kinase Akt and FoxO transcription factors. Trib3 overexpression is sufficient to induce neuron death, and silencing of endogenous Trib3 strongly protects from death when NGF is withdrawn. Mechanism studies reveal that Trib3 interferes with phosphorylation/activity of Akt and contributes to Akt i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 59 publications
(111 reference statements)
3
42
0
Order By: Relevance
“…It is worth noting that it has been reported that TRIB3-null animals show upregulation of TRIB1 and TRIB2 in at least some tissues. 39 As TRIB2 is associated with induction of acute myelogenous leukemia 40,41 and TRIB1 with other malignancies, 42,43 changes in the levels of the other Tribbles isoforms may also contribute to the phenotype observed in Trib3 À / À animals.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that it has been reported that TRIB3-null animals show upregulation of TRIB1 and TRIB2 in at least some tissues. 39 As TRIB2 is associated with induction of acute myelogenous leukemia 40,41 and TRIB1 with other malignancies, 42,43 changes in the levels of the other Tribbles isoforms may also contribute to the phenotype observed in Trib3 À / À animals.…”
Section: Discussionmentioning
confidence: 99%
“…16 A self-amplifying feedforward loop exists between Akt dephosphorylation/inactivation and FoxO dephosphorylation/activation and involves Trib3, a FoxO-induced molecule that interferes with Akt phosphorylation, thus leading to progressive FoxO activation and neuronal death. 17 In the etoposide-induced apoptosis model, Akt was rapidly decreased (at both mRNA and protein levels). Importantly, we detected increased levels of miR-711 and Akt mRNA in the RISC complex.…”
Section: Mir-711 Activates Neuronal Apoptosis B Sabirzhanov Et Almentioning
confidence: 99%
“…13,14 In contrast, Akt (protein kinase B) promotes neuronal survival by phosphorylating/inactivating pro-apoptotic proteins such as forkhead transcription factor FoxO3 and GSK3β that are important initiators of BH3-only protein expression. [15][16][17] Akt pathway inhibition leads to dephosphorylation/activation of FoxO3a and induction of its pro-apoptotic target genes including PUMA and Bim. 18,19 The present study tested the hypothesis that TBI-induced changes of selected miRs can initiate cell death pathways that result in neuronal loss and neurological deficits.…”
mentioning
confidence: 99%
“…It was identified as a novel ER stress-inducible gene that, when up-regulated, activated several genes involved in cell death during ER stress (21). Trib3 is also shown to be elevated by several stresses, including hypoxia, 6-hydroxydopamine, growth factor deprivation, anoxia, and ethanol exposure (16,(22)(23)(24)(25)(26)(27)(28). It has also been shown that Trib3 is elevated in Parkinson's disease brains and mediates neuron death in various Parkinson's disease models (27).…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…We interfered with the expression of Trib3 using previously described shRNA constructs (23). The Trib3 shRNA construct efficiently blocked induction of Trib3 by A␤ in neuronally differentiated (primed) PC12 cells (Fig.…”
Section: A␤ Treatment Induces Trib3 Mrna and Protein Levels Inmentioning
confidence: 99%